President Xi’s Soft Power “She Power” initiative’s impact on women’s maternal health and schoolgirls in Balochistan, Pakistan - Kamran Saddique; Zheng Lu; Sufyan M. Ramish; Dai Yonghong; Muhammad S. Rao (AFRICAN JOURNAL OF REPRODUCTIVE HEALTH, 2026)
This paper examines the impact of President Xi Jinping’s Soft Power “She Power” initiative on women’s maternal health and school girls’ livelihoods in Balochistan, Pakistan. Launched by the Chinese Embassy, the initiative distributes 20,000 hygiene kits and conducts health awareness campaigns for schoolgirls. Utilizing a systematic literature review and policy analysis, this study evaluates the initiative against Balochistan’s critical socio-economic indicators, including a Maternal Mortality Ratio (MMR) of 298 per 100,000 live births and a 12% female literacy rate. The findings suggest that “She Power” initiative is a notable exercise in soft power projection and a valuable Menstrual Hygiene Management (MHM — the hygienic management of menstruation, including access to sanitary materials, water, and sanitation facilities) intervention, its direct impact on systemic maternal health and women’s livelihood challenges is currently limited and indirect. The focus on schoolgirls establishes a long-term, theoretical pathway for improved reproductive health. The paper concludes that for China’s social diplomacy to achieve sustainable development impact, such initiatives must be integrated with broader, direct health and economic empowerment projects. This integration must occur within the China-Pakistan Economic Corridor (CPEC) framework to ensure measurable and lasting outcomes.